Does political instability lead to higher inflation? a panel data analysis - Veiga, Francisco José (2006)
The main purpose of this paper is to empirically determine the main causes of the worldwide diversity of inflationary experiences, a challenge not yet satisfactorily confronted by the profession for two fundamental reasons. First, empirical models explaining inflation in the literature generally fail to account for inflation inertia and for the endogeneity of important economic and political variables affecting inflation. We use system-generalized method of moments (GMM) estimation applied to dynamic panel data to address some of the econometric limitations of the OLS models previously used in the literature. Second, several political variables used as explanatory variables in earlier studies were relatively poorer.